Caracterização de segurança e tecnológica de bactérias acidoláticas termofílicas autóctones e aplicação em queijo parmesão - Santos, Cecília Loyola Afonso dos [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Autochthonous lactic acid bacteria (LAB) isolated from various food can produce enzymes, vitamins, and flavor compounds, or compounds that exhibit physiological effects. Recently, studies performed by our research group showed that some autochthonous strains isolated from water buffalo mozzarella cheese are capable of producing bacteriocin as well as some strains presented probiotic properties. In this context, the aim of this study was to evaluate the safety and technological characteristics of autochthonous thermophilic lactic acid bacteria (LAB) strains of Lactobacillus helveticus (SJRP56 and SJRP191), S. thermophilus (SJRP02, SJRP03, SJRP107 and SJRP109) and Lb. delbrueckii subsp. bulgaricus (SJRP49, SJRP50, SJRP51, SJRP57, SJRP76, SJRP149 and SJRP181). For the safety characterization of the cultures, the antibiotic resistance, the hemolytic, β-glucosidase, N-acetyl-β-glucosaminidase and β-glucuronidase activities, and the investigation of the presence of genes that characterize virulence factors, production of biogenic amines and antibiotic resistance were carried out. The technological properties: acidification kinetics, exopolysaccharide production and enzymatic activity were evaluated for all strains. For the safe strains the analyses of the casein hydrolysis and aminopeptidase activity were also performed. From the safety and technological characterization, four strains were selected: Lb. helveticus SJRP56 and SJRP191, Lb. delbrueckii subsp. bulgaricus SJRP57 and S. thermophilus SJRP107, and used in the production of Parmesan cheese. The cheese were produced in industrial scale in two independent processing using 2.3% fat pasteurized standardized milk. After cheese production, the chemical composition was determined, and during the ripening period, the physicochemical characteristics were evaluated (acidity, pH value and proteolysis). At the third month of ripening, the microbiological quality of cheese was carried out. During ...

As culturas selvagens ou autóctones isoladas de diversos alimentos podem produzir enzimas, vitaminas e compostos aromatizantes, ou ainda, compostos que apresentem efeitos fisiológicos em humanos. Estudos recentes realizados pelo nosso grupo de pesquisa mostraram que algumas cepas autóctones isoladas de muçarela de búfala são produtoras de bacteriocinas, e outras apresentam características probióticas. Neste contexto, o objetivo do trabalho foi avaliar as características de segurança e tecnológicas de treze cepas autóctones de bactérias acidoláticas (BAL) termófilas de Lactobacillus helveticus (SJRP56 e SJRP191), S. thermophilus (SJRP02, SJRP03, SJRP107 e SJRP109) e Lb. delbrueckii subsp. bulgaricus (SJRP49, SJRP50, SJRP51, SJRP57, SJRP76, SJRP149, SJRP181). Para a caracterização de segurança das culturas foram verificadas a susceptibilidade a antibióticos, a atividade hemolítica e das enzimas β-glucosidase, N-acetil-β-glucosaminidase e β-glucuronidase, e a presença de genes que caracterizam fatores de virulência, produção de aminas biogênicas e resistência a antibióticos. As propriedades tecnológicas: cinética de acidificação, produção de exopolissacarídeos e atividade enzimática, foram avaliadas para todas as cepas. Para as cepas consideradas seguras também foram realizadas as análises da hidrólise da caseína e a atividade de aminopeptidases. A partir da caracterização de segurança e tecnológica foram selecionadas quatro cepas: Lb. helveticus SJRP56 e SJRP191, Lb. delbrueckii subsp. bulgaricus SJRP57 e S. thermophilus SJRP107 para aplicação na produção de queijo Parmesão. Os queijos foram produzidos em escala industrial em dois processamentos independentes, utilizando-se leite pasteurizado e padronizado com 2,3% de gordura. Foi determinada a composição centesimal dos queijos após a produção, e durante o período de maturação foram avaliadas as características físico-químicas...
Keywords: Tecnologia de alimentos; Alimentos - Microbiologia; Bactérias gram-positivas - Aplicações industriais; Segurança alimentar; Queijo parmesão; Food Microbiology